The Lifecycle of the 47% - Don Fullerton; Nirupama Rao (Center for Economic Studies and ifo Institute (CESifo), 2016)
We assess the concentration and duration of zero tax liabilities and of transfer receipts, using data for households with ten to forty years of observations from the Panel Survey of Income Dynamics. We find that neither is strongly concentrated. Nearly 68% owe no federal tax in at least one year, approximately 78% receive some type of transfer in at least one year, and more than 58% receive transfers other than Social Security in at least one year. Of those who do not owe federal tax in any given year, 18% pay tax the following year, and 39% contribute within five years. Of those who receive transfers other than Social Security within a given year, nearly 44% stop receiving such transfers the next year, and more than 90% stop within ten years.
Keywords: H23; H24; 330; taxation; transfers; social security; EITC; unemployment compensation; AFDC; TANF